16 Rezolvați ecuațiile:
a) 2(x+1)+3(x-2)-5=266-2x)+15;
B) 2(2x - 3)-3(5-3x)=3(x+3) - 4(x+4).
Damaya:
la a e bine 266-2x?
Răspunsuri la întrebare
Răspuns de
4
a) 2(x+1)+3(x-2)-5=2(6-2x) + 15
2x+2 +3x-6-5= 12-4x+15
5x-9 = -4x+27
5x+4x = 27+9
9x = 36
x = 36/9 =4
b) 4x-6 -15+9x= 3x+9 -4x-16
13x-21 = -x -7
13x+x = -7+21
14x = 14
x= 14/14 = 1
Alte întrebări interesante
Engleza,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Fizică,
9 ani în urmă
Limba română,
9 ani în urmă